Neuromuscular Electrical Stimulation Induces Skeletal Muscle Fiber Remodeling and Specific Gene Expression Profile in Healthy Elderly - Mancinelli, Rosa; Toniolo, Luana; Di Filippo, Ester Sara; Doria, Christian; Marrone, Mariangela; Maroni, Camilla Reina; Verratti, Vittore; Bondi, Danilo; Maccatrozzo, Lisa; Pietrangelo, Tiziana; Fulle, Stefania (Frontiers in Physiology, 2019)
Skeletal muscle aging is a multifactorial process strictly related to progressive weakness. One of the results that were focused on was the fiber phenotype modification and their loss. The physiological muscle recruitment to contraction, basically prosecuted under volitional control, can also be engaged by means of Neuromuscular Electrical Stimulation (NMES). Knowing that the NMES is effective in improving muscle strength in active healthy elderly, the aim was to investigate which physiological modifications were able to produce in the Vastus lateralis muscle and the pathways involved. It was found that NMES increased the cross sectional area and the isometric strength of type II myofibers together with the activated myogenic pathway in order to shift glycolytic toward the oxidative phenotype II myofibers, at a molecular level and with an increase of maximal voluntary contraction (MVC) at a functional level. Using the TaqMan low density array on 48 different genes, we found that NMES specific gene regulation highlighted: (i) increased protein synthesis with respect to protein degradation; (ii) the activation of an apoptotic pathway involved in the differentiation process; (iii) increased regeneration signals; (iv) oxidative enzyme regulation. These pathways were validated via confirmatory RT-PCR for genes involved in the regeneration process as well as Myosin isoforms. We also investigated the oxidative stress status analyzing superoxide anion levels, the protein expression of two different superoxide dismutase and the activity of both catalase and superoxide anion dismutase, being two main antioxidant enzymes. In conclusion, data demonstrates that NMES is effective in producing physiological adaptation on Vastus Lateralis of active healthy elderly as well as providing new insights for further research on elderly who experienced muscle detriment for periodic or permanent immobility.